Uso del programa microsoft office powerpoint como recurso didáctico para fortalecer el aprendizaje de polígonos del bloque de geometría en los estudiantes de noveno grado de educación general básica del colegio nacional Luis G. Tufiño de la parroquia San Andrés, del cantón Chinchipe, provincia de Zamora Chinchipe, periodo 2013-2014 - Jiménez Jiménez, María Susana (2015)
The present investigation was undertaken to determine the PROGRAM OF MICROSOFT OFFICE POWERPOINT application RESOURCE TRAINING TO STRENGTHEN THE LEARNING OF ESTATES BLOCK GEOMETRY IN NINTH GRADE STUDENTS OF GENERAL BASIC EDUCATION. The research responded to a descriptive design (diagnosis) and experimental pre; phases that were used in that order were: Comprehensive, at this stage a mind map, a content plan was developed and theoretically substantiated each descriptor content plan on learning of polygons; diagnosis, diagnostic assessment of learning polygon using criteria and indicators was made and taken up in polls these criteria and indicators were applied to the freshmen of EGB and teaching of mathematics; modeling was defined, a procedural performance analysis was conducted and implementation plans for the effective use of Microsoft Office PowerPoint program as a teaching resource to enhance learning of polygons were designed; application, defined the Microsoft office PowerPoint as a teaching resource proceeded to its implementation through workshops; and assessment, once applied workshops effectiveness of Microsoft office PowerPoint in strengthening the learning of polygons with Wilcoxon rank sign test was evaluated. The main findings in this research were: Difficulties or cognitive deficits present in the learning needs of polygons, can reduce or mitigate the application of Microsoft office PowerPoint program as a teaching resource.